Socioeconomic and geographic variation in coverage of health insurance across India - Ambade, Mayanka; Rajpal, Sunil; Kim, Rockli; Subramanian, S. V. (Frontiers in Public Health, 2023)
In India, regular monitoring of health insurance at district levels (the most essential administrative unit) is essential for its effective uptake and thus contain the high out of pocket health expenditures. In the lack of individual data on health insurance coverage at district levels in India, we use the unit records of households from the latest round (2021) of the nationally representative National Family Health Survey to calculate the weighted percentage (and 95% CI) of households with at least one member covered by any form of health insurance and its types across socio-economic characteristics and geographies of India. Further, we used a random intercept logistic regression to measure the variation in coverage across communities, district and state. Such household level study of coverage is helpful as it represents awareness and outreach for at least one member, which can percolate easily to the entire household with further interventions. We found that only 2/5th of households in India had insurance coverage for at least one of its member, with vast geographic variation emphasizing need for aggressive expansion. About 15.5% were covered by national schemes, 47.1% by state health scheme, 13.2% by employer provided health insurance, 3.3% had purchased health insurance privately and 25.6% were covered by other health insurance schemes (not covered above). About 30.5% of the total variation in coverage was attributable to state, 2.5% to districts and 9.5% to clusters. Religion, caste, place of residence, household-size, gender, marital status, and age of household head all show a weak gradient.